1995
DOI: 10.1099/13500872-141-9-2053
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes exists in at least three evolutionary lines: evidence from flagellin, invasive associated protein and listeriolysin O genes

Abstract: Regions of the genes encoding flagellin (flaA), the invasive associated protein (iap), listeriolysin 0 (My) and 235 rRNA were sequenced for a range of Listeris monocytogenes isolates of different origin and serotypes. Several nucleotide sequence variations were found in the flaA, iap and hly genes. No differences were found for the rRNA genes, but our approach does not exclude the existence of differences between single copies of these genes. Based on the sequence differences, the L. monocytogenes strains can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
144
1
10

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 29 publications
13
144
1
10
Order By: Relevance
“…Although there was also a difference in the numbers of repeated sequences between 1E1 and 2E1, which were serotype 1/2b strains isolated in August and November, respectively, there were only two nucleotide substitutions between these strains. Taken together, comparison of the sequences among the same serotype isolates showed that the differences were mostly limited to the numbers of repeated sequences; this has previously been reported in detail as the polymorphic region of iap [10]. The obtained genetic similarity likely persistent contamination of L. monocytogenes around the area investigated in this study.…”
mentioning
confidence: 54%
“…Although there was also a difference in the numbers of repeated sequences between 1E1 and 2E1, which were serotype 1/2b strains isolated in August and November, respectively, there were only two nucleotide substitutions between these strains. Taken together, comparison of the sequences among the same serotype isolates showed that the differences were mostly limited to the numbers of repeated sequences; this has previously been reported in detail as the polymorphic region of iap [10]. The obtained genetic similarity likely persistent contamination of L. monocytogenes around the area investigated in this study.…”
mentioning
confidence: 54%
“…PCR detection of known L. monocytogenes virulence genes, such as inlA, inlB, actA, hlyA, plcA and plcB, has not proven suitable for differentiation of virulent and avirulent isolates (Nishibori et al, 1995), as these genes are consistently found in L. monocytogenes (Jaradat et al, 2002). Genetic lineage analysis has some predictive value for L. monocytogenes pathogenicity; however, the correlation between genetic lineages and pathogenicity is not consistent for all strains (Piffaretti et al, 1989;Rasmussen et al, 1995;Wiedmann et al, 1997). …”
Section: Introductionmentioning
confidence: 99%
“…Two phylogenetic lineages were identified initially by multilocus enzyme electrophoresis (Piffaretti et al, 1989), and the existence of these lineages was subsequently confirmed by partial DNA sequencing of a virulence gene (Rasmussen et al, 1991), PFGE (Brosch et al, 1994) and ribotyping (Graves et al, 1994). Rasmussen et al (1995) provided the first evidence of a third L. monocytogenes phylogenetic lineage, lineage III, based on analyses of partial DNA sequences for flaA, iap and hly. Ribotyping and PCR-RFLP analyses of L. monocytogenes virulence genes, as well as comparative genomics and DNA sequencing studies, further confirmed the existence of at least three phylogenetic lineages in L. monocytogenes (Doumith et al, 2004;Ward et al, 2004;Wiedmann et al, 1997).…”
Section: Introductionmentioning
confidence: 99%